Microservices and DevOps: Achieving Scalability and Agility in Cloud Architectures - Ganore, Pramod (International Journal of Computing and Engineering, 2021)
The convergence of Microservices Architecture (MSA) and DevOps has revolutionized cloud computing by enabling scalability, agility, and resilience in modern applications. Traditional monolithic architectures often struggle with operational inefficiencies, scalability bottlenecks, and deployment rigidity. Microservices, by decomposing applications into independent, loosely coupled services, enhance modularity and scalability. DevOps fosters collaboration between development and operations, leveraging Continuous Integration/Continuous Deployment (CI/CD), Infrastructure as Code (IaC), and automated monitoring to streamline software delivery. This article explores the synergistic relationship between Microservices and DevOps, detailing how their integration optimizes cloud-native architectures. Key benefits include automated scaling, rapid deployment, fault tolerance, and improved developer productivity. Challenges such as service orchestration, data consistency, security risks, and increased operational complexity persist. The article also examines industry case studies, including Netflix, Uber, and financial institutions, that have successfully implemented microservices with DevOps to achieve high availability and performance. Emerging trends such as serverless computing, AIOps, and edge computing are reshaping the future of microservices and DevOps.